Metabolic diversity and responses of anteater clostridial isolates to chitin-based substrates - Amin, Ahmad; Modrackova, Nikol; Tejnecky, Vaclav; Neuzil-Bunesova, Vera (Frontiers in Veterinary Science, 2025)
AimClostridium species, such as Clostridium perfringens, C. baratii, C. colicanis, Paraclostridium bifermentans, and Paeniclostridium sordellii, are Gram-positive, anaerobic, endospore-forming bacteria with diverse pathogenic mechanisms. While these species are commensals in the guts of variable animal species, such as anteaters, they are less frequently found in humans. The diet of anteaters, which includes chitin and formic acid, plays an important role in their specific dietary habits, as well as in clostridial metabolism.Methods and resultsThis study investigates the metabolic diversity and responses of anteater clostridial isolates to various substrates, namely chitin, chitosan, cellulose, N-acetyl-D-glucosamine (NAG), and glucose. All tested clostridia were able to grow in the presence of chitin, cellulose, NAG, and glucose, but varied in metabolite production. However, the presence of chitosan surprisingly showed an antimicrobial effect against clostridia, especially Pae. sordellii, P. bifermentans, and C. colicanis. The results demonstrate significant variations in fermentation profiles, and metabolite production across substrates and clostridial species. Acetate production was detected as common for all tested clostridia despite species variability and incoming substrates, as well as lactate, butyrate, propionate, and formate for some strains.ConclusionIn relation to digestion, anteater clostridia could play an important role in chitin and its degradation products, which, in the end, can influence clostridial occurrence and pathogenicity via chitosan.